Identification and expression analysis of cinnamyl CoA reductase gene family and function of StCCR6 in potato (Solanum tuberosum L.) - Du, Chong; Che, Yunzhu; Zhang, Zengli; He, Fumeng; Zhang, Xinqi; Han, Yujie; Yang, Zelin; Wang, Jiaqi; Qi, Tianshuai; Lan, Ying; Wang, Yingnan; Li, Fenglan (Frontiers in Plant Science, 2025)
Cinnamoyl-CoA reductase (CCR), a key rate-limiting enzyme in plant lignin biosynthesis, critically regulates plant growth, development, and abiotic stress responses. As one of the world’s four major staple crops, potato (Solanum tuberosum L.) is extensively cultivated due to its nutritional value and versatile applications, underscoring the importance of investigating the StCCR gene family and its expression patterns under abiotic stress. In this study, we identified 10 CCR genes from the Atlantic potato genome and conducted comprehensive analyses of their phylogenetic relationships, gene structures, species collinearity, cis-regulatory elements, and expression specificity. Virus-induced gene silencing (VIGS) was used to silence StCCR6, resulting in altered lignin content and enhanced susceptibility to bacterial infection. Results revealed structural and functional divergences among StCCRs members. Tissue-specific expression profiling demonstrated higher transcript abundance in stems and leaves compared to roots. Notably, StCCRs exhibited differential expression patterns across multiple stress conditions, with Subfamily I genes showing consistent upregulation under various treatments, suggesting their potential as core candidates mediating stress-responsive lignification. Silencing of StCCR6 altered lignin content and cell wall structure in potato, and the oxidative damage was more serious after bacterial infection. These findings establish a foundation for elucidating the functional roles of StCCRs in potato growth regulation and stress adaptation mechanisms.